Behind the flexibility: insufficient occupational injury protection of gig workers in China - Ran, Xiaoxing; Zhao, Ying (Frontiers in Public Health, 2023)
Objective: Occupational injury protection is essential to safeguard the basic rights of workers. This article focuses on a group of gig workers who have emerged on a large scale in recent years in China and aims to explore their status of occupational injury protection. Methods: Based on the theory of technology-institution innovation interaction, we adopted the institution analysis to assess the work-related injury protection of gig workers. The comparative study was used to evaluate three cases of occupational injury protection in China for gig workers. Results: Institutional innovation failed to respond to technological innovation and provided insufficient occupational injury protection for gig workers. The work-related injury insurance was inaccessible to gig workers due to they were not treated as employees in China. The work-related injury insurance was available to gig workers. Although some practices were explored, shortcomings remain. Conclusions: Behind the flexibility of gig work is insufficient occupational injury protection. According to the theory of technology-institution innovation interaction, we believe the reform of work-related injury insurance is increasingly essential for improving the situation of gig workers. This research contributes to expanding understanding of gig workers' situation and may offer a reference to other countries on protecting gig workers against occupational injuries.